2017
DOI: 10.1002/aic.15779
|View full text |Cite
|
Sign up to set email alerts
|

Impact of osmotic agent on the transport of components using forward osmosis to separate ethanol from aqueous solutions

Abstract: The separation of low molecular weight organic compounds such as the ethanol from aqueous solutions represents an important area to be investigated and increment the range of applications of forward osmosis. This investigation assesses the effects of using different draw solutes for ethanol separation from dilute aqueous solutions. The influence of glucose, sucrose, sodium chloride, and magnesium chloride was evaluated in terms of total permeate, reverse solute and ethanol fluxes. Inorganic solutes promoted hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Using a similar membrane, different results were obtained by Ambrosini et al who demonstrated the possibility to preferentially removing alcohol from a feed solution (dealcoholisation). This study performed with lower initial alcohol concentration in the feed (5%) described how draw selection can impact relative alcohol/water passage through the membrane, organic draw solutes being preferred to favour alcohol permeation [ 69 ]. The same research team also investigated the impact of membrane type (CTA and TFC membranes from HTI) on the separation process [ 70 ].…”
Section: Applications Of Fo As Concentrating Processmentioning
confidence: 99%
“…Using a similar membrane, different results were obtained by Ambrosini et al who demonstrated the possibility to preferentially removing alcohol from a feed solution (dealcoholisation). This study performed with lower initial alcohol concentration in the feed (5%) described how draw selection can impact relative alcohol/water passage through the membrane, organic draw solutes being preferred to favour alcohol permeation [ 69 ]. The same research team also investigated the impact of membrane type (CTA and TFC membranes from HTI) on the separation process [ 70 ].…”
Section: Applications Of Fo As Concentrating Processmentioning
confidence: 99%
“…Such beverages can be made using biological and physical methods. With the latter, several approaches have been reported including pervaporation , vacuum distillation , thin film evaporation , dialysis , reverse osmosis , spinning cone column distillation , osmotic distillation , membrane distillation and forward osmosis . All those methods have intrinsic disadvantages, the most common of which is the loss of aromatic volatile compounds, which usually exceed 75% of higher alcohols and 95% of esters , resulting in beer with reduced alcoholic, solvent and fruity aromas .…”
Section: Introductionmentioning
confidence: 99%